Influence of Feminism on Fashion in United States of America - Williams, Oliver (International Journal of Fashion and Design, 2023)
Purpose: The study sought to analyze the influence of feminism on fashion in United States of America Methodology: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that recent fashion history is intertwined with women's empowerment through the progressive decrease of sexual double standards, which still prevailed at the beginning of the 20th Century. The evolution of fashion has accompanied women's empowerment, first through functionalizing women's clothes, then through feminizing the power symbol represented by the male suit. Throughout history, women were not given the autonomy to decide their clothing choices. They were made to wear tight corsets and uncomfortable garments that quite literally put a curb on their movement and symbolically on their freedom. Unique Contribution to Theory, Practices and Policies: The Feminist theory and Tickles-across theory may be used to anchor future studies in the fashion sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of the fashion industries in the country will also use the study findings to improve sociology and ensure high and stable performance in all their activities and programs. The study recommends that the adoption of effective fashion development policies in feminism will help to improve efficiency in their major operations and activities.